Kristietības kritika Ēriha Fromma darbos - Eihmanis, Mārtiņš (Latvijas Universitāte, 2008)
Baklaura darba mērķis ir izvērst Ēriha Fromma idejas kristietības kontekstā. Darbā iekļauts Fromma lielāko darbu apskats tieši no reliģijas pozīcijām. Apskatītie darbi ir – „Psychoanalysis and Religion”, „Escape from Freedom”, „The Dogma of Christ”, „Psihoanalīze un Dzenbudisms”, „Mīlestības Māksla”, „Beyond the Chains of Illusion” un „Man for Himself”. Tāpat sīkāk tiek apskatīta Fromma analītiskās sociālpsiholoģijas pētniecības metode un tās pielietojums. Darba centrālā tēma ir Fromma interpretācija par kristietības rašanos un attīstību laika posmā 0-300 g. Tāpat tiek apskatīta Fromma interpretācija par kristīgās tradīcijas izmaiņām reformācijas laikā Martina Lutera un Džona Kalvina ideju kontekstā.

The objective of the Bachelor’s Thesis is to explore the ideas of Erich Fromm in the context of Christianity. This Thesis contains review of most widely known works of E. Fromm from the view point of Christianity. The following works are reviewed: „Psychoanalysis and Religion”, „Escape from Freedom”, „The Dogma of Christ”, „Psychoanalysis and Zen Buddhism”, „The Art of Loving”, „Beyond the Chains of Illusion” and „Man for Himself”. Also the method of Fromm’s analytic social psychology has been explored and analyzed. The major thrust of the work is a close examination of Fromm’s interpretation of the raise and development of Christianity in the time period 0 – 300 year of the Common Era. Also, Fromm’s interpretation of the changes within the Christian tradition during the time of Reformation in the context of the ideas of Martin Luther and John Calvin have been discussed.
Critics of Christianity in Erich Fromm's works
Keywords: Teoloģija un reliģiju zinātne